Structural modification and antibacterial property studies of natural chalcone sanjuanolide - Zhai, Jiadai; Li, Shucheng; Fu, Lin; Li, Chuang; Sun, Bingxia; Sang, Feng; Liu, Hongliang (Frontiers in Chemistry, 2022)
Clinical infections arised from multidrug-resistant bacteria pose a serious threat to human and global public health. Moreover, due to very few antibiotics discovered, there is an urgent need to develop new antibacterial agents to combat antimicrobial resistance challenges. In this study, a series of new chalcone derivatives bearing 3′-hydroxyisoprenyl moiety were prepared employing Claisen-Schmidt condensation as key step by combinatorial chemistry, and overall yields of these novel derivatives are in the range of 28–68% in the two-step reaction. Sanjuanolide and the synthesized derivatives have been investigated for their expected antibacterial activities against Gram positive bacteria (Staphylococcus aureus CMCC 26003) as well as Gram negative bacteria (Escherichia coli CMCC 44102). Among these compounds, only 4c (MIC = 12.5 μg/mL) and 4d (MIC = 25 μg/mL) exhibited obviously antibacterial activity comparable to Sanjuanolide (MIC = 12.5 μg/mL, against S. aureus CMCC 26003), and the results of subsequent in vivo experiments on Sanjuanolide suggest that Sanjuanolide exhibit bacteriostatic and bactericidal effects by altering cellular structure, disrupting the integrity of cell membranes, and reducing outer membrane potential.